2020
DOI: 10.24275/rmiq/bio947
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma Asperellum, an inoculant for production of steviol glycoside in Stevia Rebaudiana bertoni plants micropropagated in a temporary immersion bioreactor

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Stevia (Stev) based sweeteners are natural, and highly acceptable in the market. These compounds are extracted from the plant Stevia rebaudiana, and the compounds of interest are known as steviol glycosides (Carocho et al, 2017;Villamarín-Gallegos et al, 2020). Also, Stev is reported to have beneficial effects linked to adjuvant metabolic syndrome diseases such as type 2 diabetes (Philippaert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Stevia (Stev) based sweeteners are natural, and highly acceptable in the market. These compounds are extracted from the plant Stevia rebaudiana, and the compounds of interest are known as steviol glycosides (Carocho et al, 2017;Villamarín-Gallegos et al, 2020). Also, Stev is reported to have beneficial effects linked to adjuvant metabolic syndrome diseases such as type 2 diabetes (Philippaert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that biotization with endophytes on M. spicata microplants was effective, reducing the disease incidence to 8% for T. asperellum and 10% for B. subtilis , making it an alternative to conventional soil inoculation methods. According to [ 24 , 25 ], this method allows a better and faster interaction with the root system and a higher growth induction. It has been shown that although endophytes live in close association with plants, they need to overcome defense barriers such as specialized plant metabolites [ 26 ]; so, these microorganisms need to produce enzymes that break them down and can colonize tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic bacteria, such as B. subtilis , can protect plants by producing antibiotics that inhibit pathogen development and promote induced systemic resistance (ISR) [ 31 ]. Inoculation of endophyte microorganisms during micropropagation is an alternative that can improve crop quality and increase the content of specialized metabolites such as flavonoids and phenolic compounds in general [ 25 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was recovered, placed in Eppendorf tubes, and stored at −4 °C until the analysis by HPTLC (CAMAG, Switzerland). The quantification of SGs was based on the methodology reported by Bladt & Zgainski (1996) and Morlock et al (2014) , and described recently by Villamarin-Gallegos et al (2020) . Stevioside and rebaudioside A concentration were expressed in mg g DW −1 .…”
Section: Methodsmentioning
confidence: 99%